2021
DOI: 10.3390/ijms222312627
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells and Basophils in the Defense against Ectoparasites: Efficient Degradation of Parasite Anticoagulants by the Connective Tissue Mast Cell Chymases

Abstract: Ticks, lice, flees, mosquitos, leeches and vampire bats need to prevent the host’s blood coagulation during their feeding process. This is primarily achieved by injecting potent anticoagulant proteins. Basophils frequently accumulate at the site of tick feeding. However, this occurs only after the second encounter with the parasite involving an adaptive immune response and IgE. To study the potential role of basophils and mast cells in the defense against ticks and other ectoparasites, we produced anticoagulan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Almost an identical pattern of cleavage was seen for these two anticoagulants indicating that the connective tissue MC proteases cleave the anticoagulants of a broad array of different ectoparasites ( 92 ). Interestingly, the mucosal MC proteases were in general inactive against these anticoagulant proteins indicating a high selectivity of these proteases in their target specificity ( 92 ). Connective tissue MCs are primarily located in the skin which is the primary site of infection for these ectoparasites, indicating a functional adaptation of the cleavage specificity to targets of importance for the particular type and tissue location of the MC.…”
Section: In Vivo Targets For the MC Chymasesmentioning
confidence: 96%
See 2 more Smart Citations
“…Almost an identical pattern of cleavage was seen for these two anticoagulants indicating that the connective tissue MC proteases cleave the anticoagulants of a broad array of different ectoparasites ( 92 ). Interestingly, the mucosal MC proteases were in general inactive against these anticoagulant proteins indicating a high selectivity of these proteases in their target specificity ( 92 ). Connective tissue MCs are primarily located in the skin which is the primary site of infection for these ectoparasites, indicating a functional adaptation of the cleavage specificity to targets of importance for the particular type and tissue location of the MC.…”
Section: In Vivo Targets For the MC Chymasesmentioning
confidence: 96%
“…We tested their activity on the thrombin inhibitors hirudin from Hirudum medicinalis and on anophelin from the malaria vector Anopheles gambiae. Almost an identical pattern of cleavage was seen for these two anticoagulants indicating that the connective tissue MC proteases cleave the anticoagulants of a broad array of different ectoparasites (92). Interestingly, the mucosal MC proteases were in general inactive against these anticoagulant proteins indicating a high selectivity of these proteases in their target specificity (92).…”
Section: Role In the Defense Against Ectoparasitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, RmS-3 may be a key component in modulating the early steps of inflammatory reactions by blocking the chymase which is generated during mast cell activation ( Coutinho et al., 2020 ). Chymase also appears to be crucial for the degradation of tick anticoagulants, so its inhibition should help the tick to maintain blood fluidity ( Fu et al., 2021 ). A recent study showed that the serpin IRS-2 of I. ricinus can inactivate almost all connective tissue chymases from a range of animals, including human, hamster, rat, dog, and opossum, as well as mucosal mast cell proteases, rat blood vessel chymases, and also neutrophil proteases.…”
Section: The Importance Of Tick Salivary Serpins In Tick-host Interac...mentioning
confidence: 99%
“…A recent study showed that the serpin IRS-2 of I. ricinus can inactivate almost all connective tissue chymases from a range of animals, including human, hamster, rat, dog, and opossum, as well as mucosal mast cell proteases, rat blood vessel chymases, and also neutrophil proteases. However, this serpin fails to inactivate mast cell tryptases and the basophil-specific protease mMCP-8 ( Fu et al., 2021 ). The first study of the tick serpin IRS-2 disclosed the protein as having a preferential specificity for chymase and cathepsin G and as having a significant anti-inflammatory effect in vivo by reducing swelling and neutrophil migration into inflamed tissues, while a later study showed that IRS-2 reduced spirochete Borrelia burgdorferi -induced IL-6 production in splenic dendritic cells ( Chmelar et al., 2011 ; Páleníková et al., 2015 ).…”
Section: The Importance Of Tick Salivary Serpins In Tick-host Interac...mentioning
confidence: 99%